Therapeutic Drug Monitoring of Infliximab in Iraqi Patients with Moderate to Severe Ulcerative Colitis - Hussein Hazim Saleh; Dheyaa J. Kadhim; Raghad Jawad Hussein (Iraqi Journal of Pharmaceutical Sciences, 2025)
The term "inflammatory bowel disease" refers to a group of gastrointestinal tract inflammatory disorders that are considered idiopathic, chronic, and relapsing. The two primary disorders that comprise inflammatory bowel disease are Crohn's disease and ulcerative colitis. Infliximab, a chimeric monoclonal antibody, is a medication used to treat a number of autoimmune diseases such ulcerative colitis, Crohn’s disease, rheumatoid arthritis, and psoriasis. Therapeutic drug monitoring is a tool used in therapeutic decision-making that allows dosage modifications to be made in accordance with clinical and laboratory measures, usually blood concentrations of the drug, in order to achieve the drug exposure linked to the best response rate. The trough concentrations of infliximab at 3 to 7 μg/mL is most effective at inducing remission in patients with inflammatory bowel disease. The aims of the current study were to determine the achievement of trough level target, development of antidrug antibodies to Infliximab, assess response to therapy and to study trough level relation with different variables in patients with ulcerative colitis. The present study was cross-sectional conducted at ‟Gastroenterology and Hepatology Teaching Hospital/ Medical City / Baghdad / Iraq” during May 2022 to November 2022. Forty candidate patients with ulcerative colitis were included [Males =20 (50%), Females=20 (50%)] with median age [32.00 (28.50-40.75) years]. According to trough level, disease activity and development of antibodies, escalation of the dose were recommended for 10 patients (25%), switching therapy were recommended for 16 patients (40%), and continuation of the same dosage regimen were recommended for 14 patients (35%). In addition, results of current study showed that age, body mass index, and packed cell volume were significantly higher and erythrocyte sedimentation rate was significantly lower in in patients achieved target infliximab trough level compared to those not achieved. By using multivariate binary regression analysis only age and erythrocyte sedimentation rate can be used to predict the achievement of target trough level of infliximab. In conclusion, therapeutic drug monitoring of infliximab to determine the trough level and antidrug antibodies can explain the possible causes of non-responsiveness to this drug among ulcerative colitis patients with subsequent recommendations based on these findings.